Avaliação por competências: um estudo de caso em uma empresa estatal no segmento de energia - Souza, Edna Alves Bezerra de (2011)
As an answer to changes stemming from the scene of fierce competitiveness of business, which characterized the turn of the twenty-first century, organizations begin to take into account the perspective of its employees´ competences. This research aims at identifying how the process of evaluating core competencies in an organization takes place. The starting point is to perceive how individual and organizational skills are defined. By the use of a qualitative research approach, the methodology united both content analysis of public data from a state enterprise and the analysis of data obtained through interviews and questionnaire to employees from strategic areas within the company. The results of this analysis indicate that, when assessing the performance of its employees, through a perspective of personnel management, the company might benefit from better organizational results in terms of quality and productivity and is also enabled it to be able to align their business goals and skills to the company´s see developed in their staff. Developing a deeper knowledge about business practices with respect to skills assessment provides a basis for future discussions dealing with the academic skills assessment as a business practice and at the same time, allows managers to incorporate this practice, with the possibility that it may provide better results to their organizations